Student wellbeing in Qatar: a systems thinking approach to educational, societal, and cultural challenges - Hessa Al-Thani (Frontiers in Education)
IntroductionThis study investigated the challenges affecting sustainable student well-being in Qatar, with a specific emphasis on educational, societal, and cultural dimensions. Using Systems Thinking to conceptualize the interconnected nature of these challenges, the study aimed to analyze how these domains collectively impact student well-being.MethodsData were gathered from focus groups involving key stakeholders, including educators, parents, and policymakers. The discussions were analyzed to identify complex relationships and patterns across the educational, societal, and cultural domains.ResultsEducational challenges included systemic deficiencies, inadequate curricula, and a lack of opportunities for critical and creative thinking. Societal challenges encompassed social stereotyping, adverse social conditions, and insufficient familial support for progressive education. Cultural challenges highlighted issues related to identity, values, and the influence of a rentier mindset. The study revealed a fragmented educational system hindered by a lack of unified vision and professional development opportunities, along with societal constraints that impede intellectual growth. Additionally, concerns were raised over the erosion of cultural identity and religious values, exacerbated by Western educational norms and the dominance of English over Arabic. Rapid economic growth in Qatar has also led to increased materialism and individualism, affecting social cohesion.DiscussionAddressing these challenges requires a comprehensive approach that integrates educational reforms, societal support, and cultural preservation. The findings provide valuable insights for policymakers and educators seeking to enhance sustainable student well-being and create a more holistic educational environment in Qatar.